EXPLORATION OF PROCEDURAL KNOWLEDGE IN SOLVING ARITHMETIC OPERATION IN FRACTION OF GRADE XI STUDENTS AT SMAN 17 IN MAKASSAR - Siami Prafitriyani (Universitas Negeri Makassar, 2016)
Exploration of Procedural Knowledge in Solving Arithmetic Operation in Fraction of Grade XI Students at SMAN 17 in Makassar (supervised by Suradi Tahmir and Awi Dassa).The study aims at exploring procedural knowledge of grade XI students at SMAN 17 Makassar in solving arithmetic operation in fraction. The type of this study is explorative research with qualitative in nature. The subjects of the study were grade XI students at SMAN 17 Makassar with the total of 4 people. Data were collected by conducting written test and interview. Data were analyzed using qualitative data analysis which covered data reduction, data presentation, triangulation technique, and conclucing drawing. Data validity was conducted by employing triangulation technique. The result of the study reveals that only one out of four subject arranged and use algorithm in solving the questions by implementing appropriately; whereas, in evaluation questions, those four subjects did the counting aligned with the rules of counting the fraction.